ANALISIS REFORMASI BIROKRASI DALAM PERSPEKTIF TRANSFORMASIONAL KINERJA DOSEN DI SEKOLAH TINGGI PENERBANGAN INDONESIA CURUG TANGERANG - Sunarno; Solihin (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
The research aims to contribute and changes through reform of the bureaucracy associated with the performance of lecturers and the development of science to the Indonesian Aviation High School institution, except that this study also aims to determine the development of faculty performance in STPI through leadership and motivational variables. Thus, to know the perspective of the 107 respondents surveyed overall number of lecturers, just taken as many as 52 respondents using techniques slovin. Assuming that the error value is used by 10%. The research method uses descriptive quantitative approach, using the techniques of statistical data analysis, correlation, determination, t test and the F test (ANOVA) assisted with software SPSS (Statistical Product And Service Solutions). Results of analysis show that there is a leadership influence on the performance of lecturers by 25% while the remaining 75% are influenced by other factors. Besides, there is also the effect of motivation on the performance of lecturers by 20.6% while the remaining 79.4% influenced by other factors. Taken together that leadership and motivational lecturer affect the performance of 36.5% for the remaining 65.5% is influenced by other factors